1991
DOI: 10.1207/s15327655jchn0803_4
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Needs of Primary Caregivers of Home-Hospice Clients

Abstract: The purpose of this study was to assess the self-perceived needs of primary caregivers of terminally ill home-hospice clients. A home interview was conducted using an instrument based on the Neuman Systems Model. Data were analyzed in relation to intrapersonal stressors (within the individual), interpersonal stressors (between the individual and others), and extrapersonal stressors (between the individual and the environment). Five community nursing diagnoses (Porter, 1987) were identified: (a) Population at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Our results are congruent with the hospice and palliative care philosophy of promoting holistic well-being of patients and their families. Types of strain evident in this quantitative study also resonate with domains emerging from qualitative interviews with family caregivers at end of life (e.g., Decker & Young, 1991;Jansma, Schure, & de Jong, 2005).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our results are congruent with the hospice and palliative care philosophy of promoting holistic well-being of patients and their families. Types of strain evident in this quantitative study also resonate with domains emerging from qualitative interviews with family caregivers at end of life (e.g., Decker & Young, 1991;Jansma, Schure, & de Jong, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…All three appraisals predicted higher cumulative strain. These results argue for greater consideration of caregivers' appraisals in end-of-life research, an argument also made by others (e.g., Decker & Young, 1991;Haley et al, 1996;Oberst et al, 1989). Appraisals can be used to identify caregivers who are likely to experience greater strain.…”
Section: Conclusion About Caregiver Appraisalssupporting
confidence: 54%
See 1 more Smart Citation
“…Family caregivers not only assist in care alongside providers of palliative care services but also provide the bulk of support within the home (Decker & Young, 1991;Ferrell, 1998;Kurtz et al, 1995;Rhodes & Shaw, 1999). Without the input of family caregivers, the well-being of the majority of individuals with a life-threatening illness would be compromised (Stetz & Brown, 1997).…”
mentioning
confidence: 99%
“…In the circumstances, the caregiver has many needs. It leads to stress for the caregiver if their needs related to the responsibility of caregiving are not met [20,21]. Sintayehu, et al 2015 reported that overall prevalence of mental distress among caregiver 56.7%.…”
Section: Normal Line Of Defensementioning
confidence: 99%